Rancang Bangun Sistem Informasi Persediaan Barang Berbasis Website di Toko Bangunan Cahaya Abadi Nagreg - Kirana, Nita (Jurnal Dimamu, 2024)
Cahaya Abadi Nagreg Shop is a shop that operates in the field of selling construction materials. In the process of handling building materials warehouses, manual processing is still used. Therefore, it requires an optimal system to increase operational efficiency. The design of a building materials inventory information system is a system that will be built to minimize the problems faced in the building materials inventory information system. The methodology used in this Building Material Inventory Information System is Object Oriented (OOAD) and uses the Rational Unified Process (RUP) model and is supported by the Unified Modeling Language (UML) for a well-structured software engineering process. With a stock recording system, errors when recording or losing item data can be minimized, transactions become faster, then orders can be made both offline and online.